The public health implications of assisted reproductive technologies - Deonandan, Raywat (Université d'Ottawa | University of Ottawa, 2010)
Objective:The public health implications of Assisted Reproductive Technologies (ART) are largely unknown by researchers and policy makers alike. Outcomes need to be considered, not just as clinical issues, but in terms of effect on public health. Methods: Using a qualitative key informant process involving interviews with selected professionals and a review of the medical literature, eight general themes of public health issues associated with ART were identified, and are discussed. Recommendations: Short and long-term health outcomes of women undergoing ART procedures, and of their offspring, need to be considered, as do the epidemiological risks associated with donated gametes and the effect on health services of multiple and preterm births, both produced in higher rates by ART. A national surveillance system and greater inter-jurisdictional communication are important strategies for addressing these evolving concerns.
Keywords: public health, reproductive medicine, review literature, infant, IVF, ART, in vitro fertilization